2010
DOI: 10.1787/5kmfp51f5f9t-en
|View full text |Cite
|
Sign up to set email alerts
|

Health Care Systems

Abstract: This paper presents a set of indicators to assess health care system performance. It also presents new comparative data on health care policies and institutions for OECD countries. This set of indicators allows the empirical characterisation of health care systems and the identification of groups of countries sharing similar health institutions. It also helps to uncover strengths and weaknesses of each country's health care system and assessing the scope for improving value-for-money. The empirical analysis su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
26
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(26 citation statements)
references
References 37 publications
0
26
0
Order By: Relevance
“…Their regression analysis indicated that it can account for about 90% (R 2 = 0.94) of the variation in spending across the 30 OECD countries in 2001 although the results of this paper appear to be suggest this figure is around 60% (R 2 = 0.97) for the same 30 OECD countries in 2009 (regression 2). However, in their regression Luxembourg and Norway were excluded as "Luxembourg's GDP is unusually high from international financial services, and Norway's is unusually high by virtue of its oil revenues" (Reinhardt, Hussey, & Anderson, 2004) The results show that after controlling for differences in GDP and healthcare quality/outcomes through life expectancy, there are some significant differences between the six groups of OECD countries in 2009 that share similar healthcare institutions identified by Joumard, André, & Nicq (2010). This therefore suggests that healthcare institutions do play a significant role in determining healthcare spending.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Their regression analysis indicated that it can account for about 90% (R 2 = 0.94) of the variation in spending across the 30 OECD countries in 2001 although the results of this paper appear to be suggest this figure is around 60% (R 2 = 0.97) for the same 30 OECD countries in 2009 (regression 2). However, in their regression Luxembourg and Norway were excluded as "Luxembourg's GDP is unusually high from international financial services, and Norway's is unusually high by virtue of its oil revenues" (Reinhardt, Hussey, & Anderson, 2004) The results show that after controlling for differences in GDP and healthcare quality/outcomes through life expectancy, there are some significant differences between the six groups of OECD countries in 2009 that share similar healthcare institutions identified by Joumard, André, & Nicq (2010). This therefore suggests that healthcare institutions do play a significant role in determining healthcare spending.…”
Section: Discussionmentioning
confidence: 99%
“…The institutional differences between healthcare systems in terms of market structures, competition levels, and government intervention and their role on healthcare spending can be explored by looking for evidence of differences between the six groups of countries sharing similar healthcare institutions identified by Joumard, André, & Nicq (2010). The specifics of how they grouped the 29 countries being covered earlier in the literature review section.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Others (including Denmark, Norway, and Poland) re-centralised responsibilities, citing concerns about heightened equity problems, potentially insufficient local funding to finance future heath care needs, duplication and inefficiency and other reasons (Saltman, 2008). Decentralisation could make the health care system more responsive to local needs and promote innovation, but it may also result in institutional complexity, weakening control over spending and insufficient exploitation of economies of scale (Joumard et al, 2010). A careful assessment is required.…”
Section: Potential Reform Options For Better Allocation Of Roles and mentioning
confidence: 99%